Web-Based Laundry Services Information System On Rizky Laundry: Sistem Informasi Jasa Laundry Berbasis Web Pada Rizky Laundry - Ananto Yan Bachtiar; Sumarno (Universitas Muhammadiyah Sidoarjo, 2021)
Laundry service is one of the services that is quite commonly used today, this service can help people who don't have time to wash their clothes. Rizky laundry is an example of a laundry service that is developing in the Dharmawangsa area, Surabaya. The system used in Rizky Laundry still uses manual data which make it difficult to find customer data. Such conventional systems can cause operational ineffectiveness and are prone to data loss. Based on this description, the authors have the idea to create a Web-Based Laundry Service Information System at Rizky Laundry. It is hoped that this information system can help for transactions and can make it easier for Rizky Laundry to create customer data and reports.